PERAN MANAJER PERSONALIA DALAM MEMOTIVASI KERJA KARYAWAN DI PT AKSARA SOLOPOS SURAKARTA - Shafina Arum Miladia; Tri Murwaningsih; Patni Ninghardjanti (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
Abstract The purpose of this research is to find out: Roles, obstacle and solutions of personnel manager in motivating employee’s work at PT Aksara Solopos Surakarta. The method used in this research is descriptive qualitative research method with a case study research approach. The results of research showed that: The role of the personnel manager in motivating the work of employees at PT Aksara Solopos Surakarta includes providing direction to employees, providing good examples for employees, personnel manager as employee counselors, and as activator positive working conditions; The obstacle faced by personnel managers in motivating employees' work includes several individual employee had a bad character and less problem solving solution form field managers; Solutions made by personnel managers to overcome obstacles in motivating employees' work include providing rewards and punishments and approaching employees.